From DVB-S to DVB-S2X: Progress in Standardization of Digital Satellite Broadcasting Systems - K. Yu. Kolomensky; A. Yu. Demidova; A. S. Kazarinov (Известия высших учебных заведений России: Радиоэлектроника, 2024)
Introduction. The article presents a brief history of the European and international standardization process in the field of digital video broadcasting (DVB) systems as applied to satellite broadcasting. The advantages of new systems are considered. The results of a comparative analysis of their main characteristics in relation to previous versions are given.Aim. To study the current progress in the standardization of digital satellite broadcasting systems, to analyze their new features and capabilities, to compare their main characteristics, and to distinguish the advantages of new systems in relation to previous versions.Materials and methods. Documents of the European Telecommunications Standards Institute (ETSI) and the International Telecommunication Union related to the standardization of satellite broadcasting systems from DVB-S to DVB-S2X were studied. A comparative analysis of the main functions and characteristics of the systems under consideration was carried out.Results. New functions and features introduced in the DVB-S2 system were analyzed, including the Time-Slicing (Annex M) option, which allows receivers to select and decode a specific stream carrying one or more services of interest without wasting resources on processing other streams. New DVB-S2X system options were considered, including the SuperFraming Structure (Annex E) option, which ensures increased immunity to co-channel interference from neighboring beam signals, as well as support for future developments related to beam hopping. The advantages of channel aggregation in DVB-S2X were illustrated, which allows the capacity of two or three transponders to be shared in order to increase the statistical multiplexing ratio in the case of UHDTV programs.Conclusion. The standardization of digital satellite broadcasting systems provides an opportunity for equipment developers and manufacturers to use the latest technologies and methods, while relying on internationally recognized standards. This allows, on the one hand, the equipment of digital satellite broadcasting systems and the consumer quality of the services provided to be constantly improved, and, on the other hand, the cost of chips and equipment produced to be optimized.